The Effectiveness of Monopoly Media to Improve Learning Outcomes in Integrative Thematic Learning at SD Negeri Tegalsari 01 Semarang (Universitas Negeri Semarang, 2020)
The purpose of this study is to analyze the effectiveness of the Monopoly media learning media on the ability of understanding the place value with two digit numbersand the results of thematic learning in grade 1 elementary school students. The subjects of this study were grade 1 students at SD Negeri Tegalsari 01 and class B which has 24 students acted as the control group. This study was used quasi experimental design method with nonequivalent control group design. The results of the study on the understanding ability towards the place value with two digit numbersand thematic learning outcomes show the average score of initial test scores in the experimental group is 7.13 and the control group is 7.34. Meanwhile, for the average score of final test scores in the experimental group is 8.09 and the control group is 7.50. Based on these results, it appears that the Monopoly media can effectively improve the learning outcomes of the control group by marked enhancement in these results. The conclusion of this research is that the use of Monopoly game as learning media can effectively improve the results of thematic learning on the lesson of recognizing the living and non-living objects around us and explain the value of the place consisting two numbers. In addition, Monopoly can effectively influence the understanding of the place value with two digit numbers. From the results of this study, it is recommended for teachers to use Monopoly as media in the learning process.